Constitutional de novo deletion CNV encompassing REST predisposes to diffuse hyperplastic perilobar nephroblastomatosis (HPLN). Issue 9 (11th September 2020) - Hyder, Zerin; Fairclough, Adele; Groom, Mike; Getty, Joan; Alexander, Elizabeth; van Veen, Elke M; Makin, Guy; Sethuraman, Chitra; Tang, Vivian; Evans, D Gareth; Maher, Eamonn R; Woodward, Emma R
Abstract : Background: Nephroblastomatosis is a recognised precursor for the development of Wilms tumour (WT), the most common childhood renal tumour. While the majority of WT is sporadic in origin, germline intragenic mutations of predisposition genes such as WT1, REST and TRIM28 have been described in apparently isolated (non-familial) WT. Despite constitutional CNVs being a well-studied cause of developmental disorders, their role in cancer predisposition is less well defined, so that the interpretation of cancer risks associated with specific CNVs can be complex. Objective: To highlight the role of a constitutional deletion CNV (delCNV) encompassing the REST tumour suppressor gene in diffuse hyperplastic perilobar nephroblastomatosis (HPLN). Methods/results: Array comparative genomic hybridisation in an infant presenting with apparently sporadic diffuse HPLN revealed a de novo germline CNV, arr[GRCh37] 4q12(57, 385, 330–57, 947, 405)x1. The REST tumour suppressor gene is located at GRCh37 chr4:57, 774, 042–57, 802, 010. Conclusion: This delCNV encompassing REST is associated with nephroblastomatosis. Deletion studies should be included in the molecular work-up of inherited predisposition to WT/nephroblastomatosis. Detection of delCNVs involving known cancer predisposition genes can yield insights into the relationship between underlying genomic architecture and associated tumour risk.